From Plantations to Ports: Unraveling the Drivers of Indonesia’s Palm Oil Competitiveness in Key Asia and Africa Markets (2005-2024) - Ascariena Rafinda; Siti Resmi; Alga Aprila Dwi Purwito (Business, Accounting and Management Journal, 2026)
Palm oil is a strategic commodity and a major non-oil and gas export contributor for Indonesia, which is the world's leading exporter. This study aims to analyze the influence of macroeconomic variables on Indonesia's palm oil export performance and assess its competitiveness in five key Asian and African markets: China, India, Egypt, Pakistan, and Singapore, over the period 2005–2024. A quantitative approach was employed, utilizing panel data regression (Fixed Effect Model) to test macroeconomic factors and the Revealed Comparative Advantage (RCA), Export Product Dynamics (EPD), and Trade Specialization Index (TSI) for competitiveness analysis. The results show that the Gross Domestic Product (GDP) and Inflation in importing countries have a positive and significant effect on palm oil exports, consistent with increasing aggregate purchasing power and inelastic demand for this essential commodity. Conversely, the Real Exchange Rate (RER) was found to be statistically insignificant. Competitiveness analysis confirmed Indonesia's strong market position. The RCA index indicated a strong comparative advantage across all markets, with the product categorized as a 'Rising Star' via the EPD in China, India, Egypt, and Pakistan. The consistently high TSI values (0.98 to 1.00) further affirm Indonesia's strong and persistent role as a net exporter. These findings underscore the need for adaptive and sustainable export policies to maintain Indonesia’s competitive advantage in the volatile global trade landscape.